Transmission mechanism in a developing economy: does money or credit matter? - Mohamed, Azali (Universiti Putra Malaysia Press, 2001)
This book covers empirical and policy oriented studies. It contents provide a through exposition of economic theory to shed light on real issues in understanding a developing country economy. The book is structured in an easy reading manner that makes it ideal for all levels of researchers, especially for the postgraduate students who are researching in the applied macroeconomics area.